Self-Reported Knowledge Levels of Critical Care Nurses in Managing Neuroemergencies: A Survey Based Study. (1st September 2019) - Amlani, Karan; Nelson, Sonia; Riley, Elka; Hickman, Zachary L; Kellner, Christopher P; Weiss, Nirit; Almufti, Fawaz; Bohaene, Golda; Bederson, Joshua B; Mocco, J D; Dangayach, Neha
Abstract: INTRODUCTION: Neurocritical care has become increasingly subspecialized. However, due to a lack of bed availability in neurocritical care units (NCCUs), sometimes patients may need to be boarded in other intensive care units (ICUs). Several academic centers do not have access to dedicated NCCUs. We hypothesized that general ICU and postanesthesia care unit (PACU) nurses may not feel as comfortable managing neurocritical care patients. In this survey-based quality improvement (QI) study, we explored the self-reported knowledge of ICU and PACU nurses at a comprehensive stroke center in recognizing and managing some common neurological emergencies such as stroke, status epilepticus, and raised intracranial pressure. METHODS: We engaged the nursing managers of 8 units in this QI project, which included medical, surgical, neurocritical care, cardiac and cardiothoracic units as well as PACU and interventional radiology units. Using institutional RedCap, anonymized surveys were sent to the nurses in January 2019. We collected information on demographic and critical care work experience. All participants answered questions on a Likert-type scale based on their knowledge of several common neurological emergencies. RESULTS: A total of 240 nurses (199 females, 41 males) participated in the survey. Out of which, 112 (58%) had been working in an ICU for 3 yr or longer. Their self-reported level of knowledge in managing neurological emergencies have been summarized below. More than half the participants did not feel comfortable managing patients with EVDs, ICH, SAH, raised intracranial pressure, and TBI and traumatic spine injury patients. More than 70% of nurses were not satisfied with their current level of training to deal with neuroemergency and supported the need for dedicated training/study time. CONCLUSION: ICU and PACU nurses report gaps in knowledge in recognizing and managing common neuroemergencies. With an increasing cohorting of patients in subspecialized units, it is important to provide ongoing education to ICU and PACU nurses to help them maintain fundamental neurocritical knowledge.